2022
DOI: 10.1111/jam.15621
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial levels and diversity in kitchen sponges and dishwashing brushes used by consumers

Abstract: Aims:The purpose of the work was to investigate bacterial levels and diversity as well as survival of Salmonella in used dish washing sponges and brushes and identify consumer practices that can potentially explain bacterial status of these items. Methods and Results:Used washing up utensils were collected from consumers.The bacterial numbers (TVC) were very variable with an extremely high median level (10.3 log cfu/item) in Portuguese sponges and lower levels in Norwegian items (7.3 and 7.0 cfu/item for spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Although the households in the current study had considerable differences with respect to kitchen standards (households with and without running water, indoor sink, and dish washing machine), food preparation routines, and dietary habits ( 23 25 ), we still found a set of core bacteria resident in the kitchen environment. Also, similar bacteria were found in European kitchens as were previously found in other kitchen surfaces and kitchen sponge studies ( 2 , 7 , 12 15 ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Although the households in the current study had considerable differences with respect to kitchen standards (households with and without running water, indoor sink, and dish washing machine), food preparation routines, and dietary habits ( 23 25 ), we still found a set of core bacteria resident in the kitchen environment. Also, similar bacteria were found in European kitchens as were previously found in other kitchen surfaces and kitchen sponge studies ( 2 , 7 , 12 15 ).…”
Section: Discussionsupporting
confidence: 86%
“…We found that Acinetobacter was present in all countries and samples and that its relative abundance was high (especially in humid samples such as sponges, cloths, and sinks) and not significantly different between countries. We have previously also reported that Acinetobacter was among the most dominant bacteria in used sponges and brushes across different countries in Europe ( 12 ), and Adams et al ( 2 ) reported that Acinetobacter was abundant in kitchens regardless of geographic location (South Korea, Colorado, North Carolina). One explanation for the dominance of Acinetobacter in kitchens could be that it probably enters the kitchen daily, since it is highly occurrent on vegetables, meat, fish, and milk and appears to be persistent in drinking water systems ( 29 31 ).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations